PENYULUHAN HUKUM PENTINGNYA KEPEMILIKAN SERTIFIKAT TANAH TENTANG PENDAFTARAN TANAH DI DESA KEDUNGBOTO KEC. LIMBANGAN KAB. KENDAL - A. Saiful Aziz (SOSIO DIALEKTIKA : JURNAL ILMU SOSIAL HUMANIORA, 2019)
Abstract The certificate is a proof of rights which is valid as a proof of strong ownership of physical data and juridical data contained in the measuring certificate and land book of the relevant rights in accordance with Article 19 Paragraph (2) of the LoGA. In practice in the community it turns out that the certificate of land rights is not the only proof of ownership of land rights, but old rights such as girik and receipts are proof of ownership of land rights, which are based on Article 24 paragraph (1) PP 24 of 1997 Problems to be resolved in this study (1) how the legal power of land rights certificates (2) what efforts can be made to ensure legal certainty in the land sector. Keyword: Certificate, ownership, legal power